Assessment of Stroke Patients' Muscle Strength Following a Combination of Mirror Therapy and ROM (Range of Motion) Exercises Based on Self-Care Theory - Nadatien, Ima; Salamah, Umi Leka; Hidaayah, Nur (Poltekkes Kemenkes Surakarta, 2024)
Background: When blood flow problems kill off some brain cells, the result is a neurological deficiency known as a stroke. There have been 507 reported cases of stroke in East Java, while the overall stroke prevalence in Indonesia has jumped from 7% to 10.9% (Riskesdas, 2020). The researchers at RSI Darus Syifa's Surabaya set out to determine how much of an impact self-care theory-based mirror therapy and range-of-motion exercises had on the muscular strength of stroke patients admitted to the inpatient unit. Methods: A true experimental with a pretest-posttest control group design was utilised in this type of research. One hundred and ten stroke patients made up the study's population. There were a total of 34 participants in this study, with 17 serving as control subjects and 17 as interventionists. Sampling was based on probability sampling using simple random sampling. The Medical Research Council (MRC) scale was utilised by the device to measure muscular strength. Mann-Whitney and the Wilcoxon Signet Rank Test were used to examine the collected data. Results: In the inpatient ward of the Darus Syifa Surabaya Hospital, stroke patients who undergo a combination of mirror therapy and range of motion exercises based on self-care theory show a significant improvement in muscle strength, according to the Mann-Whitney test (p < 0.05). Conclusion: The study found that stroke patients' muscle strength improved with a combination of mirror therapy and range of motion exercises grounded in self-care theory.